Season, weather and predictors of healthcare-associated Gram-negative bloodstream infections: a case-only study. Issue 2 (February 2019) - Rodrigues, F.S.; Clemente de Luca, F.A.; Ribeiro da Cunha, A.; Fortaleza, C.M.C.B.
Summary: Background: Recent studies reported seasonality in healthcare-associated infections (HCAI). The association of this phenomenon with other risk factors for HCAI is not clear. Aim: To analyse the interplay of season, weather and usual predictors of healthcare-associated bloodstream infections caused by Gram-negative bacilli (GNB-BSI). Methods: A case-only study was conducted in a teaching hospital in Brazil. The study enrolled 446 subjects with GNB-BSI diagnosed from July 2012 to June 2016. Demographic data, comorbidities, invasive procedures and use of antimicrobials were reviewed in medical charts. The season in which GNB-BSI occurred, and weather parameters on the day of diagnosis were recorded. Factors associated with occurrence of GNB-BSI in different seasons (reference category: winter) and caused by different GNB (reference category: Escherichia coli ) were analysed. Uni- and multi-variable models of multi-nomial logistic regression were used for analysis. Findings: GNB-BSI diagnosed in summer was more likely to be caused by Klebsiella spp. [odds ratio (OR) 5.33; 95% confidence interval (CI) 2.04–13.96] or Acinetobacter baumannii (OR 2.69; 95% CI 1.04–6.96), and there was an association between Klebsiella spp. and spring (OR 2.86; 95% CI 1.14–7.18). Average temperature on the day of diagnosis was associated with Klebsiella spp. (OR 1.19; 95% CI 1.07–1.33) and A. baumannii (OR 1.20; 95% CI 1.07–1.34). Conclusion: Warm seasons and daily temperature impact on the aetiology of GNB-BSI, even in models adjusted for usual risk factors. One possible explanation for these findings is that seasonality of healthcare-associated pathogens is intrinsic to micro-organisms, and not associated with comorbidities, procedures or use of antimicrobials.